Caliber of Intracranial Arteries as a Marker for Cerebral Small Vessel Disease - Chen, Zhaoyao; Li, Hui; Wu, Minghua; Chang, Cheng; Fan, Xinying; Liu, Xinfeng; Xu, Gelin (Frontiers in Neurology, 2020)
Background: The dilation of intracranial large arteries caliber, may transfer more hemodynamic burden to the downstream brain capillaries, which, in the long run, results in cerebral small vessel disease (CSVD). This study aimed to investigate the relationship between intracranial artery calibers and small vessel disease. Methods: Patients with first-ever ischemic stroke of lacunar infarction subtype were enrolled via Nanjing Stroke Registry Program. An intracranial arterial Z-score, named the brain arterial remodeling (BAR) score, was calculated by averaging the calibers of the seven main intracranial arteries. Among the enrolled patients, those with a BAR score < -1 SD were deemed to have small intracranial artery calibers; those with a BAR score >1 SD were deemed to have large intracranial artery calibers and those with a between BAR score were deemed to have normal intracranial artery calibers. Imaging markers of CSVD, including lacuna, white matter hyperintensity (WMH), enlarged perivascular spaces (EPVS) and cerebral microbleeds (CMBs) were rated and then summed to obtain a total CSVD score. Results: A total of 312 patients were involved in this study, patients with BAR score >1 SD were older (P=0.039), and more prone to having a history of myocardial infarction (P=0.033). The Spearman’s rank correlation coefficient between the BAR score and total CSVD score is 0.320 (P<0.001). Binary logistic regression found that BAR score >1 SD was correlated with lacuna (OR=1.987; 95% CI, 1.037-3.807; P=0.039); severe WMH (OR=1.994; 95% CI, 1.003-3.964; P=0.049); severe EPVS (OR=2.544; 95% CI, 1.299-4.983; P=0.006) and CSVD (OR=2.997; 95% CI 1.182-7.599; P=0.021). Ordinal logistic regression analysis found that age (OR=1.028; 95% CI, 1.007-1.049; P=0.009), hypertension (OR=3.514; 95% CI, 2.114-5.769; P<0.001) and BAR score >1 SD (OR=2.418; 95% CI, 1.350-4.330; P=0.003) were correlated with the total CSVD score. Conclusions: Patients with large intracranial arterial calibers may have heavier CSVD burden. The mechanisms of this association warrant further study.